Medical degradable composite material lattice structure and preparation method thereof

Through silk fiber reinforced lattice structure design of degradable polymer-based composite materials, the problem of insufficient mechanical properties and energy absorption characteristics of existing materials is solved, and the composite lattice structure with high mechanical properties and excellent energy absorption properties is achieved, with good biomedical application potential.

CN119795685AActive Publication Date: 2025-04-11BEIHANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510012611.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing degradable medical polymer materials have shortcomings in terms of mechanical properties and energy absorption characteristics, and it is difficult to meet the structural stability and degradation needs of implants in the biomedical field.

Method used

Silk fiber reinforced degradable polymer-based composite materials are used to prepare dot matrix structures through mesh weaving and stamping processes to improve the mechanical properties and energy absorption characteristics of the material.

Benefits of technology

The high mechanical properties and excellent energy absorption properties of the composite lattice structure are achieved, making it have application potential in the field of biomedical products and promoting the degradation of materials in vitro and in vitro.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795685A_ABST
    Figure CN119795685A_ABST
Patent Text Reader

Abstract

The invention discloses a medical degradable composite material lattice structure and a preparation method thereof. The lattice structure is composed of an upper panel, a lower panel and a lattice core. The upper panel and the lower panel are both made of silk fabric reinforced degradable thermoplastic polymer matrix composite materials, and the dot matrix core is made of one-way silk fiber bundle reinforced degradable thermoplastic polymer matrix composite materials. The dot matrix core is formed by periodically arranging a plurality of pyramid-shaped unit cells, and each unit cell is a pyramid-shaped integrated piece composed of four rod pieces. The preparation method of the dot matrix core comprises the following steps: preparing a silk grid fabric, carrying out sizing and drying on the fabric, and carrying out punch forming. The used silk fibers have balanced elastic modulus, tensile strength and elongation at break, the strength and toughness of the composite material can be effectively improved, and the prepared lattice structure has excellent compression resistance and energy absorption characteristics. In addition, the silk fibers have water absorption, cell affinity and bone tissue compatibility, and the in-vivo and in-vitro degradation rate of the composite material can be adjusted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials and structures, and in particular to a composite material lattice structure applied in the biomedical field and a preparation method thereof. Background Art

[0002] The biomedical field, especially the field of tissue engineering, is in urgent need of degradable biomaterials and implants with ideal mechanical and biological properties. In view of tissue injuries such as trauma and sports injuries in young and middle-aged people, tissue engineering strategies propose the use of degradable implants, which can not only meet the structural stability of the injured part, but also completely degrade and achieve tissue replacement within a certain period, avoiding secondary surgery, reducing patient pain and reducing medical costs. Degradable medical polymer materials such as polylactic acid (PLA) and polycaprolactone (PCL) have good biocompatibility and degradability, and have been widely used in degradable implant devices. However, the mechanical properties of these degradable polymer materials have obvious disadvantages. For example, PLA materials have low toughness and are prone to fragmentation after implantation; PCL materials have low mechanical strength and are easy to deform, making it difficult to meet structural support requirements. In addition, implants need to resist impact loads during exercise during use, so excellent energy absorption and impact resistance are also one of the necessary conditions.

[0003] The lattice structure is an ordered open-pore structure composed of periodic units, which has the characteristics of light weight and high strength. The pore size and pore density of the lattice structure vary widely, and it is highly designable. Its internal pores are interconnected, which is convenient for cell migration, blood penetration, and the transport of nutrients. Therefore, the lattice structure has broad application prospects in the field of tissue engineering. The apparent density and modulus of traditional materials can be adjusted through lattice structure design, thereby increasing the mechanical compatibility between the implant and the surrounding tissue. The patent with application number CN113231644A is based on the apparent density and modulus of the Ti6Al4V alloy lattice material microstructure designed based on Wolfe's law, which is mechanically compatible with human cortical bone, alleviating the stress shielding effect. The patent with application number CN113304312A is based on Kagome's micro-lattice skull repair material, and adjusts its microstructure and mechanical properties to make it more compatible with the real skull. Although the porous structure / lattice structure of medical metal materials such as titanium alloys can alleviate stress shielding in bone tissue applications to a certain extent, their intrinsic modulus and non-degradability, which are much higher than those of biological tissues, may induce inflammation, leading people to expect to obtain alternative materials with lower modulus. On the other hand, although the lattice structure of polymer-based composite materials is widely used in engineering and has related patents, there are few reports on lattice structures based on degradable medical polymer materials.

[0004] In response to the above-mentioned needs for medical degradable materials and implants, the present invention proposes to use natural silk to reinforce degradable polymer materials to prepare degradable polymer-based composite materials, and further prepare a lattice structure, so that the composite material lattice structure has degradability, excellent mechanical properties and energy absorption characteristics, and has application potential in medical degradable materials and implants. Summary of the invention

[0005] The present invention provides a composite material lattice structure for use in the biomedical field and a preparation method thereof, wherein silk fibers are used to reinforce a degradable medical polymer matrix to improve the mechanical properties of the composite material lattice structure and to enable the lattice structure to have excellent energy absorption performance.

[0006] First, the present invention provides a medical degradable composite material lattice structure, the lattice structure is composed of an upper panel, a lower panel and a lattice core, and the lattice core is fixed between the parallel upper and lower panels;

[0007] The upper and lower panels of the composite material lattice structure are both made of silk fabric reinforced degradable polymer composite materials, and the lattice core is made of unidirectional silk fiber bundle reinforced degradable thermoplastic polymer composite materials;

[0008] The silk fabric is a plain weave fabric with orthogonal weaving of fiber bundles;

[0009] The lattice core is composed of pyramid-shaped unit cells arranged periodically, and each unit cell is a pyramid-shaped integral piece composed of four rods;

[0010] The nodes of the lattice core are plain weave structures formed by interweaving unidirectional silk fiber bundles, and the silk fiber bundles in two directions form an angle of 90°;

[0011] The unidirectional silk fiber bundle is degummed and twisted, and the twist of the fiber is 500 to 1500 twists;

[0012] The degradable thermoplastic polymer has biocompatibility and degradability, including polylactic acid (PLA), polycaprolactone (PCL), etc.;

[0013] The volume proportion of the fiber bundles in the unidirectional silk fiber bundle reinforced degradable polymer composite material is 40% to 80%.

[0014] Secondly, the present invention provides a method for preparing a lattice structure of a medical degradable composite material, comprising the following steps:

[0015] (1) Weaving unidirectional silk fiber bundles along two orthogonal directions to form a grid-like fabric, with the fibers at the grid nodes densely interwoven and unidirectional fiber bundles between the nodes;

[0016] (2) heating and melting a thermoplastic polymer, immersing the mesh fabric obtained in step (1) in the polymer melt for sizing, taking out the fabric after the fabric is completely soaked and waiting for the melt to solidify, thereby obtaining a flat mesh structure of a fiber-reinforced polymer-based composite material;

[0017] (3) According to the design requirements of the volume fraction of silk in the composite material, the number of sizing is adjusted. With each additional sizing, the volume fraction of the polymer will increase, and correspondingly, the volume fraction of silk will decrease;

[0018] (4) Designing a stamping die according to the node and connecting rod dimensions of the mesh fabric;

[0019] (5) locally heating the flat fiber-reinforced polymer composite grid structure obtained in step (2) to soften the polymer, and performing stamping molding using a stamping die to obtain a lattice core;

[0020] (6) alternately stacking and laying the silk fabric and the degradable polymer film, wherein the plain silk fabric is alternately laid along the 0° and 45° directions, and hot pressing to obtain the upper and lower panels of the lattice structure;

[0021] (7) The lattice core obtained in step (5) is heated and then bonded to the upper and lower panels obtained in step (6) to obtain a lattice structure.

[0022] Finally, the present invention provides a medical degradable composite material lattice structure prepared according to the above preparation method.

[0023] The advantages of the present invention compared with the prior art are:

[0024] The present invention uses silk fiber to reinforce the degradable polymer-based composite material. The elastic modulus, tensile strength and elongation at break of the silk fiber used are balanced, which can effectively improve the comprehensive mechanical properties of the composite material. At the same time, the energy absorption characteristics of the material are improved by combining the lattice structure design. Furthermore, silk fiber has water absorption and biocompatibility, which can promote the degradation of the lattice structure of the composite material in vivo and in vitro, and enhance its application potential in the field of tissue engineering.

[0025] The present invention adopts a grid weaving-stamping method to prepare a composite material lattice structure. On the one hand, the fibers are interwoven and distributed at the grid nodes to enhance the mechanical properties at the nodes, which can significantly reduce the delamination failure of the composite material in the pyramid lattice structure during the load-bearing process; on the other hand, the weaving process of silk fibers is mature and the stamping process is simple, which can realize low-cost and large-scale preparation of lattice structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1A composite material lattice structure is provided in one embodiment of the present invention, wherein 1 is an upper panel, 2 is a lower panel, 3 is a lattice core, and 4 is a lattice unit cell.

[0027] Figure 2 This is a schematic diagram of the design of a unidirectional silk fiber bundle mesh fabric in an embodiment of the present invention.

[0028] Figure 3 The figure is a schematic diagram of the process of preparing the lattice core by using a stamping die in an embodiment of the present invention.

[0029] Figure 4 Shown are (a) a schematic diagram of the preparation process of the upper and lower panels and (b) the prepared panels in an embodiment of the present invention.

[0030] Figure 5 Shown is a microscopic cross-sectional view of a lattice rod made of a unidirectional silk fiber composite material in an embodiment of the present invention.

[0031] Figure 6 Shown are HE tissue staining images of the rat subcutaneous implantation model of silk fiber reinforced polycaprolactone composite material and polycaprolactone material control group, including material and tissue staining images after (a) 14 days of implantation and (b) 28 days of implantation. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are shown in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0034] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0035] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0036] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0037] In the following examples and comparative examples, raw materials not otherwise specified are all commercially available products; operating steps and operating parameters not otherwise specified are all reasonably selectable by those skilled in the art based on experience.

[0038] A first aspect of the present invention provides a composite material lattice structure.

[0039] In some embodiments, Figure 1 As shown, the composite material lattice structure comprises an upper panel 1, a lower panel 2 and a lattice core 3, and the lattice core is fixedly arranged between the parallel upper panel and the lower panel;

[0040] In some embodiments, the upper panel and the lower panel of the composite material lattice structure are both made of silk fabric reinforced degradable polymer composite material, and the lattice core is made of unidirectional silk fiber bundle reinforced degradable polymer composite material;

[0041] In some embodiments, the lattice core is composed of Figure 1The structure is composed of a plurality of periodic pyramidal lattice structure unit cells 4, each unit cell being a pyramidal integral piece composed of four rods;

[0042] In some embodiments, the unidirectional silk fiber bundles at the nodes of the lattice core are interwoven and distributed to form a plain weave structure;

[0043] In some embodiments, the silk fabric is an orthogonal plain weave structure;

[0044] In some embodiments, the unidirectional silk fiber bundle is degummed and twisted, and the twist of the fiber bundle is 500 to 1500, for example, 500 twists are equal to 500 twists per meter of the fiber bundle. If the fiber twist is lower than 500, the fiber bundle will be split, affecting the fiber weaving process, and if the twist is higher than 1500, the fiber bundle will be too rigid, which is not conducive to weaving and impregnation of polymer melt.

[0045] The present invention adopts silk fiber to reinforce degradable thermoplastic polymer to prepare composite material lattice structure. The elastic modulus, strength and elongation at break of the silk fiber used are balanced, which can effectively enhance the mechanical properties of the degradable polymer and make the prepared lattice structure have excellent energy absorption characteristics.

[0046] In some embodiments, the degradable thermoplastic polymer is biocompatible and degradable. Optionally, the degradable thermoplastic polymer includes at least one of polylactic acid (PLA), polycaprolactone (PCL), and the like.

[0047] In some embodiments, the volume proportion of the fiber bundles in the unidirectional silk fiber bundle reinforced degradable thermoplastic polymer composite material is 40% to 80%, for example, 40%, 55%, 65%, or 75%.

[0048] The silk fibers used in the present invention have water absorption and cell affinity, which can improve the in vivo and in vitro degradation rate of the prepared composite material lattice structure, and are beneficial to its application in the field of tissue engineering.

[0049] In a second aspect, the present invention provides a method for preparing a composite material lattice structure for use in the biomedical field, the method comprising:

[0050] The unidirectional silk fiber bundles are woven in two directions at a 90° angle to form a grid-like fabric, including densely woven nodes and unidirectional fiber bundles connecting the nodes;

[0051] The unidirectional silk fiber bundles used in the present invention have good flexibility, and the fibers are interwoven and distributed at the grid nodes to enhance the mechanical properties of the nodes, thereby effectively reducing the probability of delamination failure at the nodes in the pyramid lattice structure.

[0052] The thermoplastic polymer is heated and melted, and the silk fiber mesh fabric is immersed in the polymer melt for sizing. After the fabric is completely soaked, it is taken out and the melt is cooled and solidified to obtain a flat mesh structure of a fiber-reinforced polymer-based composite material; the number of sizing times is adjusted according to the design requirements of the volume fraction of silk in the main load-bearing rods of the lattice structure; the obtained flat mesh structure is locally heated to soften the polymer matrix, and a stamping die is used for stamping to obtain a lattice core.

[0053] In some embodiments, the polymer material comprises polycaprolactone (PCL), and the melt slurrying method comprises the following steps:

[0054] a. Heating PCL powder / particles to above its melting point (e.g. 100°C) to obtain liquid PCL;

[0055] b. Immerse the mesh fabric in liquid PCL, remove it after the fabric is completely soaked and allow the melt to cool and solidify;

[0056] c. Repeat step b.

[0057] The silk fabric and the polymer film are alternately stacked and laid, wherein the silk fiber cloth is alternately laid along the 0° and 45° directions in sequence, and hot pressing is performed to obtain the upper and lower panels of the lattice structure.

[0058] The nodes of the lattice core are bonded to the upper and lower panels to obtain a lattice structure.

[0059] The silk fiber weaving process and stamping process used in the present invention are simple and mature, and the combination of the two can realize low-cost large-scale preparation of medical composite material lattice structures.

[0060] Example 1

[0061] A method for preparing a lattice structure of a medical degradable composite material comprises the following steps:

[0062] S1: Preparation of mesh fabric

[0063] The 19-denier silk fiber bundle with a unidirectional twist of 500 is used for weaving, and the resulting mesh fabric is shown in the figure. Figure 2 As shown, the fibers at the nodes are interwoven and distributed to form a plain weave structure, as shown in the local enlarged view.

[0064] S2: Preparation of composite flat grid structures

[0065] a. Weigh a certain mass of PCL with a molecular weight of 80,000, heat it to 120°C and keep it warm until it is completely melted;

[0066] b. Immerse the mesh fabric obtained in step S1 in the PCL melt, remove it after the fabric is completely soaked, and allow the PCL to cool and solidify at room temperature;

[0067] c. Repeat step b and slurry for 2 times. The volume proportion of fiber bundles in the obtained lattice core is 70%.

[0068] S3: Preparation of lattice structure

[0069] a. Figure 3 As shown, the stamping die and the punch are heated to 60°C and kept warm, and the node of the flat composite material grid structure obtained by S2 is placed directly below the punch of the stamping die, and the length direction of the punch forms an angle of 45° with the direction of the fiber bundle in the grid. After stamping, the grid structure is moved to the next node, and this process is repeated until all the rods are stamped to obtain a lattice core;

[0070] b. Figure 4 As shown, the silk plain fabric and the polymer film are alternately stacked and laid, wherein the silk fabric is alternately laid along the 0° and 45° directions in sequence, and hot pressed at 120°C and 0.28MPa for 30 minutes, and a composite material is obtained after cooling;

[0071] c. Cut the upper and lower panels according to the design size of the lattice sandwich structure, and locally heat the nodes of the lattice core and then hot-melt bond them with the upper and lower panels to obtain a lattice structure.

[0072] The cross-sectional microstructure of the unidirectional composite rod in the lattice core is shown in Figure 5 shown.

[0073] The in vivo biocompatibility of silk fiber reinforced polycaprolactone composites was verified using a rat subcutaneous implantation model. Figure 6 As shown in the figure, 14 days after the silk fiber reinforced polycaprolactone composite material was implanted, a thin layer of fibrous capsule formed on the outer layer of the material, indicating that a foreign body inflammatory response had occurred. However, 28 days after implantation, cells and blood vessels began to enter the material, indicating that the material had good biocompatibility and could be degraded to induce tissue regeneration.

[0074] Example 2

[0075] The unidirectional silk fiber bundle of the present invention is twisted, and the twist of the fiber is 500-1500, for example, 500 twists, 800 twists, 1000 twists, 1200 twists, and 1500 twists.

[0076] A composite material lattice structure was prepared according to the method of Example 1, except that the twist of the unidirectional silk fiber bundle was 1500 twists, and the volume fraction of the silk fiber in the composite material grid structure rod was 65%.

[0077] A method for preparing a lattice structure of a medical degradable composite material comprises the following steps:

[0078] S1: Preparation of mesh fabric

[0079] Silk fiber bundles with a unidirectional twist of 1500 and a specification of 19 deniers are selected for weaving, and the fibers at the nodes of the obtained fabric are densely interwoven and distributed to form a plain weave grid structure.

[0080] S2: Preparation of composite flat grid structures

[0081] a. Weigh a certain mass of PCL with a molecular weight of 80,000, heat it to 120°C and keep it warm until it is completely melted;

[0082] b. Immerse the mesh fabric obtained in step S1 in the PCL melt, remove it after the fabric is completely soaked, and allow the PCL to cool and solidify at room temperature;

[0083] c. Repeat step b and sizing twice, and the volume fraction of silk fibers in the resulting lattice core is 65%.

[0084] S3: Preparation of lattice structure

[0085] a. Figure 3 As shown, the stamping die and the punch are heated to 60°C and kept warm, and the node of the flat composite material grid structure obtained by S2 is placed directly below the punch of the stamping die, and the length direction of the punch forms an angle of 45° with the direction of the fiber bundle in the grid. After stamping, the grid structure is moved to the next node, and this process is repeated until all the rods are stamped to obtain a lattice core;

[0086] b. Figure 4 As shown, the silk plain fabric and the polymer film are alternately stacked and laid, wherein the silk fabric is alternately laid along the 0° and 45° directions in sequence, and hot pressed at 120°C and 0.28MPa for 30 minutes, and a composite material is obtained after cooling;

[0087] c. Cut the upper and lower panels according to the design size of the lattice sandwich structure, and locally heat the nodes of the lattice core and then hot-melt bond them with the upper and lower panels to obtain a lattice structure.

[0088] Example 3

[0089] The grid-like fabric of the present invention is slurried in a polymer melt, and the number of slurrying times can determine the proportion of the polymer matrix in the composite material, and can also conveniently adjust the volume fraction of the silk fiber in the composite material.

[0090] The composite material lattice structure was prepared according to the method of Example 1, except that the silk mesh fabric was slurried in the polymer melt for 5 times, and the volume fraction of silk fibers in the composite material was reduced to 45%.

[0091] A method for preparing a lattice structure of a medical degradable composite material comprises the following steps:

[0092] S1: Preparation of mesh fabric

[0093] Silk fiber bundles with a unidirectional twist of 500 and a specification of 19 deniers are selected for weaving, and the fibers at the nodes of the obtained fabric are densely interwoven and distributed to form a plain weave grid structure.

[0094] S2: Preparation of composite flat grid structures

[0095] a. Weigh a certain mass of PCL with a molecular weight of 80,000, heat it to 120°C and keep it warm until it is completely melted;

[0096] b. Immerse the mesh fabric obtained in step S1 in the PCL melt, remove it after the fabric is completely soaked, and allow the PCL to cool and solidify at room temperature;

[0097] c. Repeat step b and sizing for 5 times. The volume fraction of silk fibers in the resulting lattice core is 45%.

[0098] S3: Preparation of lattice structure

[0099] a. Figure 3 As shown, the stamping die and the punch are heated to 60°C and kept warm, and the node of the flat composite material grid structure obtained by S2 is placed directly below the punch of the stamping die, and the length direction of the punch forms an angle of 45° with the direction of the fiber bundle in the grid. After stamping, the grid structure is moved to the next node, and this process is repeated until all the rods are stamped to obtain a lattice core;

[0100] b. Figure 4 As shown, the silk plain fabric and the polymer film are alternately stacked and laid, wherein the silk fabric is alternately laid along the 0° and 45° directions in sequence, and hot pressed at 120°C and 0.28MPa for 30 minutes, and a composite material is obtained after cooling;

[0101] c. Cut the upper and lower panels according to the design size of the lattice sandwich structure, and locally heat the nodes of the lattice core and then hot-melt bond them with the upper and lower panels to obtain a lattice structure.

[0102] Example 4

[0103] In some embodiments, the degradable thermoplastic polymer is biocompatible and degradable. Optionally, the degradable thermoplastic polymer includes at least one of polylactic acid (PLA), polycaprolactone (PCL), and the like.

[0104] A composite material lattice structure was prepared according to the method of Example 1, except that the type of the degradable thermoplastic polymer was adjusted, the degradable thermoplastic polymer used was polylactic acid (PLA), the melting temperature was 230°C, and the heating temperature of the stamping die and the punch was 100°C.

[0105] A method for preparing a lattice structure of a medical degradable composite material comprises the following steps:

[0106] S1: Preparation of mesh fabric

[0107] Silk fiber bundles with a unidirectional twist of 500 and a specification of 19 deniers are selected for weaving, and the fibers at the nodes of the obtained fabric are densely interwoven and distributed to form a plain weave grid structure.

[0108] S2: Preparation of composite flat grid structures

[0109] a. Weigh a certain mass of PLA with a molecular weight of 50,000, heat it to 230°C and keep it warm until it is completely melted;

[0110] b. Immerse the mesh fabric obtained in step S1 in the PLA melt, and after the fabric is completely soaked, take it out and allow the PLA to cool and solidify at room temperature;

[0111] c. Repeat step b and sizing twice. The volume fraction of silk fibers in the resulting lattice core is 58%.

[0112] S3: Preparation of lattice structure

[0113] a. Figure 3 As shown, the stamping die and the punch are heated to 100°C and kept warm, and the node of the flat composite mesh structure obtained by S2 is placed directly below the punch of the stamping die, and the length direction of the punch forms an angle of 45° with the direction of the fiber bundle in the mesh. After stamping, the mesh structure is moved to the next node, and this process is repeated until all the rods are stamped to obtain a lattice core;

[0114] b. Figure 4 As shown, the silk plain fabric and the polymer film are alternately stacked and laid, wherein the silk fabric is alternately laid along the 0° and 45° directions, and hot pressed at 230°C and 0.28MPa for 30 minutes, and a composite material is obtained after cooling;

[0115] c. Cut the upper and lower panels according to the design size of the lattice sandwich structure, and locally heat the nodes of the lattice core and then hot-melt bond them with the upper and lower panels to obtain a lattice structure.

[0116] Comparative Example 1

[0117] The composite material lattice structure was prepared according to the method of Example 1, except that the twist of the unidirectional silk fiber bundle was 1500 twists, and high twist was not conducive to sizing. After sizing once, the volume fraction of the silk fiber increased to 80%.

[0118] Comparative Example 2

[0119] The composite material lattice structure was prepared according to the method of Example 1, except that the slurry was passed through 8 times to increase the volume fraction of the polymer matrix in the composite material, and the volume fraction of the fiber bundle in the composite material rod was 30%.

[0120] Test Example 1

[0121] In order to reflect the mechanical and biodegradable performance advantages of the composite material prepared by the present invention, the performance of each embodiment and comparative example was compared, and the test method was as follows:

[0122] According to the ASTM C365 / C 364M-05 method, the compression mechanical test of the composite material lattice structure was carried out on a SANS screw drive test machine, and the compression displacement rate was set to 0.01mm / s. The lattice structure consists of 3×3 unit cells and upper and lower panels. The unit cell size is 10mm×10mm×5mm (length×width×

[0123] The dimensions of the upper and lower panels are 30mm×30mm×1mm (length×width×height). Three samples of each composite material lattice structure were repeated, and the compression force-displacement curve was recorded. The compression energy absorption was calculated based on the curve area integral, and the results were averaged three times.

[0124] The in vitro degradation performance of the composite material lattice structure was tested using a single cell with a size of 10mm×10mm×5mm (length×width×height). After weighing, it was immersed in a 37°C degradation solution. The degradation solution was changed once a week. After 6 months, it was taken out, dried and weighed, and the weight loss percentage was recorded. Each sample was repeated 3 times. The degradation solution was a PBS phosphate buffer with a pH of 7.4, and 1U / mL type XIV protease and 1U / mL lipase were added.

[0125] Specific results are shown in Table 1. The results show that when the volume fraction of silk reaches 80% or more, the compression energy absorption of the composite material lattice structure is lower than that of the 70% lattice structure. The reason is that the resin content in the composite material is too low, and the bonding and stress transfer effects between fibers become poor. When the volume fraction of silk is 30% (lower than 40%), the compression energy absorption of the composite material lattice structure is low, and the poor compression resistance is caused by too little silk content. In the degradation experiment, silk degrades more slowly than the matrix resin due to its highly ordered molecular structure. The degradation weight loss of comparative example 1 in 6 months is 25.2%, and the degradation is too slow, which is not conducive to bone repair. The degradation weight loss of comparative example 2 is too much, and the degradation is too fast to maintain the mechanical microenvironment required for bone repair. Therefore, the composite material lattice structure prepared by the present invention meets the mechanical properties and degradation rate required for bone repair.

[0126] Silk volume fraction Compression energy absorption of composite material lattice structure Weight loss percentage after 6 months of in vitro degradation Example 1 70% <![CDATA[8.5×10 5 J]]> 35.6% Example 2 65% <![CDATA[7.2×10 5 J]]> 42.3% Example 3 45% <![CDATA[5.1×10 5 J]]> 57.2% Example 4 58% <![CDATA[5.8×10 5 J]]> 48.9% Comparative Example 1 80% <![CDATA[4.2×10 5 J]]> 25.2% Comparative Example 2 30% <![CDATA[2.1×10 5 J]]> >80% (material fragmentation)

[0127] The above description of the present invention is illustrative rather than restrictive. Based on the understanding of those skilled in the art, many modifications, changes or equivalents may be made within the spirit and scope defined in the claims, but they will all be within the scope of protection of the present invention.

Claims

1. A medical degradable composite material lattice structure, the lattice structure is composed of an upper panel, a lower panel and a lattice core, and the lattice core is fixed between the parallel upper panel and the lower panel; wherein: The upper panel and the lower panel are both made of silk fiber cloth reinforced degradable thermoplastic polymer composite material, and the lattice core is made of unidirectional silk fiber bundle reinforced degradable thermoplastic polymer composite material; The lattice core is composed of a plurality of periodic pyramidal lattice structure unit cells, each unit cell being a pyramidal integral piece composed of four rods; The unidirectional silk fiber bundles at the nodes of the lattice core are alternately distributed to form a plain weave structure.

2. The medical degradable composite material lattice structure according to claim 1, wherein: The silk fiber cloth is plain woven, including two silk fiber directions at 90° angles; The unidirectional silk fiber bundle is degummed and twisted, and the twist of the fiber is less than 200 turns / meter.

3. The medical degradable composite material lattice structure according to claim 1, wherein: The degradable thermoplastic polymer is selected from: polylactic acid, polycaprolactone, and other degradable polyester polymers.

4. The medical degradable composite material lattice structure according to claim 1, wherein: The volume proportion of the fiber bundles in the unidirectional silk fiber bundle reinforced degradable thermoplastic polymer composite material is 50% to 90%.

5. A method for preparing a lattice structure of a medical degradable composite material according to any one of claims 1 to 4, comprising: (1) weaving unidirectional silk fiber bundles to form a grid-like fabric, wherein the fabric includes two silk fiber directions at an angle of 90°, and the fibers at the grid nodes are interwoven to form a plain weave structure; (2) melting a thermoplastic polymer, slurrying the mesh fabric in the polymer melt, taking it out after the fabric is completely soaked, and waiting for the melt to cool and solidify to obtain a flat mesh fabric with the surface coated with the polymer; (3) adjusting the number of sizing times according to the design requirements of the volume fraction of unidirectional silk fibers; (4) Designing a stamping die according to the node and connecting rod dimensions of the mesh fabric; (5) stamping the flat grid-like fabric obtained in step (3) step by step with a stamping die according to the shortest length of the periodicity at an angle of 45° to obtain a lattice core; (6) alternately stacking and laying plain silk fabrics and polymer films, wherein the silk fabrics are alternately laid along the 0° and 45° directions, and hot pressing to obtain upper and lower panels of the lattice structure; (7) The lattice core obtained in step (5) is heated and then bonded to the upper and lower panels obtained in step (5) to obtain a medical degradable composite material lattice structure.

6. A medical degradable composite material lattice structure obtained according to the preparation method of claim 5.

Citation Information

Patent Citations

  • Ti-6Al-4V alloy dot matrix material microstructure and design method and application thereof

    CN113231644A

  • Application of micro-lattice structure

    CN113304312A

  • Method for preparing pyramid-shaped lattice sandwich plate by using fiber woven cloth

    CN101954744A

  • Method for preparing bone tissue engineering three-dimensional porous support based on graphene / silk fibroin

    CN105664260A

  • Continuous fiber thermoplastic composite lattice structure and preparation technology thereof

    CN107487001A